1998
DOI: 10.7863/jum.1998.17.7.411
|View full text |Cite
|
Sign up to set email alerts
|

High resolution sonographic determination of the normal dimensions of the intracranial extraaxial compartment in the newborn infant.

Abstract: Prominence of the extraaxial space occasionally is encountered in infants referred for ultrasonography to exclude hydrocephalus. The interpretation of this finding can be problematic. We examined the width of the extraaxial compartment in 82 normal newborn infants. Scanning technique was optimized for viewing the near field, and the extraaxial space was measured over the cerebral convexities. Correlation was made with demographic variables. Measurements varied from 0 to 3.3 mm (mean, 1.6 mm), with slight negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…In postnatal studies SCW and CCW, which reflect the subarachnoid space in frontal region, were measured with transfontanel approach with a range of 0 and 6.3 mm (Libicher and Tröger 1992; Frankel et al 1998; Narli et al 2006; Sabouri et al 2011). In another study, Libicher and Tröger suggested 3 and 4 mm as cut-off values for SCW and CCW, respectively, since these were the next integer above 95th percentile (Ghai et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In postnatal studies SCW and CCW, which reflect the subarachnoid space in frontal region, were measured with transfontanel approach with a range of 0 and 6.3 mm (Libicher and Tröger 1992; Frankel et al 1998; Narli et al 2006; Sabouri et al 2011). In another study, Libicher and Tröger suggested 3 and 4 mm as cut-off values for SCW and CCW, respectively, since these were the next integer above 95th percentile (Ghai et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Subarachnoid space width in infants has been evaluated by ultrasonography in several studies (Libicher and Tröger 1992; Lam et al 2001; Frankel et al 1998), but there is only one study which investigated the normal values in fetuses (Malinger et al 2000). The authors measured sinocortical width (SCW) and craniocortical width (CCW) in coronal section using transvaginal ultrasound (Malinger et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on healthy children, SAS was found as 1.9-5.7 mm [4,5,14]. Libicher and Tröger [9], and Frankel et al [4] found these measurements smaller than 4 mm and 3.5 mm, respectively. They suggested that 3 mm should be the upper limit over 95 P [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is often challenging for the reporting radiologist to define the limit between normal and enlarged subarachnoid spaces. However, a cranio-cortical width of more than 10mm is generally considered pathological [31,32]. Most believe that this condition is a result of immature arachnoid villi that are unable to keep up with the rate of CSF production [33].…”
Section: Ventriculomegaly: Is It Benign External Hydrocephalus Ex-vamentioning
confidence: 99%